Decentralized robust control of building structures under seismic excitations. - Ma, Tian Wei (Earthquake engineering & structural dynamics.)
Many of the control algorithms proposed for structures subjected to seismic excitations are based on a centralized design philosophy, such as the linear quadratic regulator (LQR) design. The information of all the states of the system is usually required in these methods to determine the control demand. For applications involving large scale systems, it may be more convenient to design decentralized controllers that depend only on the information of the local states for control command calculation. In this study, nonlinear decentralized robust control algorithm is proposed. The structural system is decomposed into several artificially uncoupled subsystems. The interconnections between adjacent subsystems are treated as uncertain but bounded disturbances to the subsystems. The controller associated with one subsystem determines the control command based only on the states of the local subsystem. Numerical examples of linear and nonlinear structural models are presented to demonstrate the effectiveness and robustness of the proposed controller. The traditional LQR design is used as a baseline for comparison.